PENGARUH MODAL KERJA DAN PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2017 - Meti Zuliyana (Jurnal RATRI (Riset Akuntansi Tridinanti), 2020)
The purpose of this study was to determine the effect of working capital and working capital turnover on profitability. This study takes the object of the pulp and paper sector manufacturing companies listed on the Indonesia Stock Exchange 2011-2017. This study uses secondary data with the technique of reporting documentation data, the entire population of financial reports, and a sample of reports from manufacturing companies in the pulp and paper sector listed on the Indonesia Stock Exchange 2011-2017. The data analysis technique used descriptive statistics, classic assumption test, multiple regression analysis, and hypothesis testing.The results of this study are as follows: 1) Working capital and working capital turnover simultaneously have a positive and significant effect on profitability with a result of Fcount of 9.142 and a significance value of less than 0.05 and a coefficient of determination of 38.7% while the remaining 61.3 % evidence of other variables. 2) Partially working capital has no significant effect on profitability with a result of tcount of 0.336 and a significance value greater than 0.05, while working capital turnover partially has a significant negative effect on profitability with a result of tcount -4.144 with a smaller significance value. from 0.05.Keywords: Working Capital, Working Capital Turnover, and Profitability